Analysis of portuguese residential buildings’ needs and proposed solutions - Guimarães, Erika Tinoco (2015)
The Portuguese housing sector experienced a significant growth throughout the 20th century, particularly in the last quarter, after the democratic revolution in 1974. In fact, the number of buildings built between 1970 and 1990 is more than one third of the buildings actually existing in Portugal. Therefore most of them were built before the publication of the first regulation concerning the energy efficiency in buildings. Regarding this scenario, it would be expected that rehabilitation activities would represent most of the current construction activities. However, given some remaining barriers from old social policies, this situation is not observed; actually building retrofitting is the least significant sector, accentuating the degradation level of major part of the Portuguese housing stock. Several studies show that the main problems are found in the buildings envelope elements, such as roofs and façades. Based on this context, the aim of this paper is to introduce some examples of building retrofitting systems that, adapted to the Portuguese main needs and requirements may represent sustainable solutions to overcome the identified needs of Portuguese buildings' envelope.